1996
DOI: 10.1002/(sici)1097-0274(199605)29:5<509::aid-ajim10>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Fall-related occupational injuries on farms

Abstract: We assessed risk factors for fall‐related farm injuries in a population‐based, case‐control study. Cases had to reside in a defined geographic region served by a single medical center. Multiple sources reported cases, and a special farm census enabled random selection of controls. The annual risk of farm fall injury was 7.5 (95% CI: 5.7, 10.0) per 1,000 person‐years. The crude incidence rate was higher in men, while the rate based on hours of farmwork was higher in women. In a multivariate analysis of risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…From other studies, 3,16 increased risks of agricultural injury have also been identified for those who worked more compared with fewer hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From other studies, 3,16 increased risks of agricultural injury have also been identified for those who worked more compared with fewer hours.…”
Section: Discussionmentioning
confidence: 99%
“…Information that would be useful to investigate in future studies includes variables such as weather conditions (rain, snow), housekeeping habits (surface debris, tripping hazards), type of footwear worn, history of falls, balance and gait, and the use of fall protection devices. 3,[23][24][25] Within the current design, this level of detail was not possible for every source/vehicle of injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another major cause of injuries is falls. Nordstrom et al (1996) reported annual rates of approximately 7.5 falls per 1000 person-years. According to their study (1996), the rate of fall-related injuries is higher for males (2.4 times that for females) and with longer work hours (an increase of 2% for each extra hour worked).…”
Section: Acute Injuriesmentioning
confidence: 99%
“…[1][2][3][4] In most pediatric settings, fall injuries are generally experienced while children are walking, running, or engaged in recreational activities. Falls from heights are also common and typically involve children falling from stairs, beds, and playground equipment.…”
mentioning
confidence: 99%